2011
DOI: 10.1080/00049182.2012.619957
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to Diversity: new perspectives on the ethnic geography of Brisbane, Australia

Abstract: As a consequence of changing immigration policy over the past 50 years, contemporary Australia has a culturally diverse population. Focusing on Brisbane, one of Australia's smaller immigrant-receiving cities but where some 19 per cent of the population is born overseas, this study examines attitudes to and perceptions of culturally different ethnic (non-Anglo) immigrant groups. Emphasis is placed on patterns of tolerance and intolerance for the city as a whole, both in areas of contact and in areas of minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…One possibility is that their perceptions are influenced by (perceived) changes to population diversity in their neighbourhoods and communities. Australia's population is becoming increasingly diverse, which means that individuals are more likely to come into contact and interact with others who identify as a different race or ethnicity (Forrest and Dunn 2011). This is consistent with work by Lyons (2007) who found that White residents typically report their victimisation as a PMC when it occurs in IJCJ&SD 101 Online version via www.crimejusticejournal.com © 2018 7(2) disadvantaged neighbourhoods that have greater populations of race and ethnic minorities than more wealthy neighbourhoods.…”
Section: Potential Barriers To Reporting Hate Crimesupporting
confidence: 75%
“…One possibility is that their perceptions are influenced by (perceived) changes to population diversity in their neighbourhoods and communities. Australia's population is becoming increasingly diverse, which means that individuals are more likely to come into contact and interact with others who identify as a different race or ethnicity (Forrest and Dunn 2011). This is consistent with work by Lyons (2007) who found that White residents typically report their victimisation as a PMC when it occurs in IJCJ&SD 101 Online version via www.crimejusticejournal.com © 2018 7(2) disadvantaged neighbourhoods that have greater populations of race and ethnic minorities than more wealthy neighbourhoods.…”
Section: Potential Barriers To Reporting Hate Crimesupporting
confidence: 75%
“…In the literature, social psychologists also reveal a strong link between contact and the perception of threat and feeling of 'fear', which might result in prejudice (Stephan and Stephan, 1985;Forrest and Dunn, 2011). They also indicate that in the absence of cross-cultural contact people will not have sufficient knowledge to judge an 'out-group' (a group with different cultural background from the host society) as a realistic threat (Stephan and Stephan, 1985;Forrest and Dunn, 2011). Realistic threats are defined as threats to resources such as time, money, and power.…”
Section: A Thematic Analysismentioning
confidence: 99%
“…Matejskova and Leitner (2011) in their study on Russian immigrants in eastern Berlin found that contact between local natives and Russian immigrants only re-enforced pre-existing stereotypes, prejudices and conflicts. Forrest and Dunn (2011) show that although people in more diverse places favour multiculturalism, older and less educated people are more likely to oppose immigration when confronted with others. Tolsma et al (2007) found that proximity of ethnic out-group members in the municipality reduces opposition to exogamy.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…According to social conflict theory, contact between different ethnic groups may also lead to hostility and discrimination (Wessel 2009;Forrest and Dunn 2011;Matejskova and Leitner 2011). Matejskova and Leitner (2011) in their study on Russian immigrants in eastern Berlin found that contact between local natives and Russian immigrants only re-enforced pre-existing stereotypes, prejudices and conflicts.…”
Section: Theoretical Backgroundmentioning
confidence: 99%